Territorial Intelligence: A collective opportunity for sustainable pastoral development and good rangeland governance in South Tunisia - Sghaier, Mariem; Frija, Aymen; Dhehibi, Boubaker; Fetoui, Mondher; Sghaier, Mongi (Centre International de Hautes Etudes Agronomiques Méditerranéennes, 2021)
Pastoralism is still considered an important economic and cultural aspect of the life of the Tunisian communities practicing agropastoral faming in South Tunisia. Our research on fundamental rangeland governance aspects showed that questions on “how to sustain rangelands and enhance their governance” and “how to develop pastoral areas” are highly interlinked. A research was carried out explore these linkages based on the “territorial intelligence - TI” concept. We particularly aim to explore the opportunities to apply the TI (as reflected by more efficient pastoral development investments) as a wider framework to enhance rangeland governance through more efficient pastoral development actions and investments. A mixed methodology has been used combining both social network analysis and “prospective system” method. To this end, results show that the lack of communication between the main economic actors involved in the management of collective pastoral areas, the ominance of the local authorities on pastoral development program design, and the weak autonomy of community based organizations (CBO’s) are the main challenge factors which could enhance harmony between rangeland governance and pastoral development.